'Imposed unknowns': a qualitative study into the impact of Independent Living Fund closure on users. Issue 7 (8th August 2016) - Porter, Tom; Shakespeare, Tom
Abstract: The Independent Living Fund (ILF) was a non-departmental public body funded by the Department for Work and Pensions. An efficient and popular system of support, the ILF enabled 46, 000 people between 1988 and 2015; however, in 2015 the Fund closed and local authorities (LAs) assumed sole responsibility for supporting former ILF users. This article presents the experiences of 12 former ILF users as they transition from ILF to LA support. We focus on participants' experiences of ILF and LA support, their transition from ILF to LA support, and the emotional impact of transition. Participants were universally positive about their dealings with the ILF, whilst nearly all were worried about LA provision. For most participants, the process of transfer was not smooth; participants received insufficient information and poor communication from LAs. Participants expressed anxiety and uncertainty over the future and these feelings were exacerbated by the actions of LAs during transfer.